What Cognitive Interviews Tell Us about Bias in Cross-cultural Research: An Illustration Using Quality-of-life Items. Issue 4 (November 2018) - Benítez, Isabel; Padilla, José Luis; van de Vijver, Fons; Cuevas, Amaya
This study illustrates how the cognitive interviewing (CI) method can provide qualitative evidence of item, construct, and method bias in cross-cultural research. CI was conducted with participants from the Netherlands and Spain, who responded to quality-of-life (QoL) items included in international survey research projects. Qualitative findings indicate that, at the construct level, Spanish participants were more affected by the particular wording of the item stems, which made them modify their understanding of the intended constructs while answering, whereas Dutch participants were more focused on being consistent in their responses. At the item level, differences in the interpretation of key terms in QoL items were mainly related to translation and cultural issues. Method bias was manifested in the differential use of response options and anchor labels. Results of the study support the contribution and usefulness of CI to informing about the three types of bias from a qualitative approach.